INCENTIVE STRATEGIES AND TALENT RETENTION OF FURNITURE FIRMS IN PORT HARCOURT (American Journal of Business Management, Economics and Banking, 2024)
This study examined the relationship between incentive strategies and talent retention of furniture firms in Port Harcourt. The target population comprised of furniture making firms in Port Harcourt. The accessible population for the study is one hundred and seventy-nine (179) management staffs selected from twenty (20) furniture making firm in Port Harcourt. The simple random sampling technique was adopted in selecting participants for this study. Sample size of one hundred and twenty-four (124) was obtained through the use of sample size determination formulation proposed by Taro Yamane. Two (4) testable null hypotheses were formulated and analyzed. Spearman’s Rank Order Correlation Coefficient was used to analyze the null hypotheses, with the help of Statistical Package for Social Sciences at 5% level of significance. The two null hypotheses were rejected and the alternate accepted. Indicating a significant positive relationship between the dimension of incentive strategies (non-financial strategies) and the measures of talent retention (intention to stay and intention to leave). Based on the findings of this study, we therefore conclude that there is positive relationship between incentive strategies and talent retention.